Isotomidae (Collembola) of Buryat Republic. Folsomia culter sp. nov and taxonomic value of terminalian chaetotaxy in the genus - Potapov, Mikhail; Chimitova, Ayuna (Zootaxa, 2009)
Folsomia culter sp. nov. is described from several sites in Eastern Buryatia (Russia, East Siberia). It occupies an intermediate position between the sensibilis- and fimetaria-groups of the genus. The species is well defined by the strong foil setae on the distal abdomen, by a pair of enlarged basal setae on dens, and by the relative position of sensillary and foil setae. The taxonomic value of the sensillary and “foil” chaetotaxy on the last two abdominal segments is discussed/ described for the two groups of Folsomia species.